From the abolition of slavery to Affirmative Action: political struggle for justice and democracy (Research, Society and Development, 2021)
The reflection proposed in this article focuses on three axes around justice and democracy in Brazil or their incipience. It is anchored in the public policies of Affirmative Actions, in order to think of a new socius. The first axis, injustice as standard, will deal with slavery and its abolition. The second will address the Affirmative Actions and the social rejection of public policies, especially racial quotas, and the third will analyze the theme civil society versus justice and democracy. It questions both concepts, as well as the epistemic racism and academic eurocentrism. Are universities only complying with the Quota Law or open to new knowledge? The purpose of this work is to reflect on the perspective that the social, economic, political and cultural balance depends on the broad engagement of civil society for the rights, real and symbolic, in the fight against racism. The results of this study indicate the manifestation to the emergence of new black intellectuals in the public sphere, appearances of political agenda and new epistemes. Methodologically, this study is supported by Sodré’s (2014a) synoptic method, of dialectical-qualitative character and bibliographical review, from authors such as Silvio Almeida (2019), Muniz Sodré (2014a, 2015), Françoise Vergès (2005), Michael Sandel (2012), Achille Mbembe (2018), Lélia Gonzalez (1982), Boaventura de Sousa Santos (2005), Gramsci (2007), Rancière (2018).